Open Source Projects beyond code : A Blueprint for Scalable and Sustainable Open Source Projects - Mertic, John (Packt Publishing, Limited, 2023)
Accelerate your career and make an impact by launching and running a successful open source project. Purchase of the print or Kindle book includes a free PDF eBook Key Features Understand the method and rationale for launching an open source project Explore best practices and insights for running an open source project Leverage open source projects to advance your career Book Description Open source is ubiquitous in our society, with countless existing projects, and new ones emerging every day. It follows a "scratch-your-own-itch" model where contributors and maintainers drive the project forward. Through Open Source Projects - Beyond Code, you'll learn what it takes to develop a successful, scalable, and sustainable open source project. In this book, you'll explore the full life cycle of open source projects, from inception, through launch, to maturity, and then discover how to sunset an open source project responsibly. Along the way, you'll learn the concepts of licensing, governance, community building, ecosystem management, and growing maintainers and contributors, as well as understand how other open source projects have been successful or might have struggled in some areas. You can use this book as an end-to-end guide or reference material for the future. By the end of this book, you'll be able to accelerate your career in open source. Your newly acquired skills will help you stay ahead of the curve even with the ever-evolving nature of technology. What you will learn Explore what is open source and how you can use it to accelerate your career Start an open source project while exploring its key considerations Grow, support, and manage a vast community of developers and users Build and maintain a mature and sustainable project Enable mass users and developers to downstream productization and outreach Use open source as a portfolio to build your career Understand when to end a project and conduct it responsibly Who this book is for This book is for software developers, product managers, project managers, business leaders, or general enthusiasts looking to start an open source project or currently maintaining one.